Drainage System Optimization as an Effective Flood Management Strategy in Urban Regions: A Systematic Review Utilizing PRISMA - Indah Ashlachal Ummah; Kartikaningsih, Hartati; Andrew, Mulabbi (Sustainability (STPP) Theory, Practice and Policy, 2025)
Flood disasters cause significant damage and losses in various cities around the world. One of the contributing factors is poor drainage system management. This literature review study aims to explore the effectiveness of drainage systems in addressing flood problems in major cities across the globe. The study utilizes a systematic literature review design with the PRISMA method. Data is sourced from the Scopus database. The document analysis process involves several stages: identification, screening, eligibility, and inclusion, ultimately resulting in 25 articles that align with the objectives of this study. The results indicate that there are three aspects to optimizing drainage systems as an effective flood management strategy in major cities: 1) Smart Technology-Based Drainage System Management, 2) Policy and Regulation-Based Drainage Management, 3) Community and Social Adaptation-Based Drainage Management, and 4) Geomorphology and Natural Process-Based Drainage Management. This literature review is expected to provide practical recommendations for improving drainage systems to be more adaptive and sustainable in addressing increasingly complex flood challenges in the future, particularly in Indonesia.